Ecosystem approach to semi-intensive cultivation of Penaeus vannamei - Hernández , Nancy; Guerrero-Ríos, Randi (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
The ecosystem approach to semi-intensive culture of Penaeus vannamei is crucial for understanding and managing water quality and planktonic communities in aquaculture systems. This study focuses on analyzing the interrelationship between structural and functional elements, using phytoplankton and zooplankton as bioindicators of water quality and trophic conditions. The objective is to provide detailed information on the dynamics of these communities in culture systems, which will improve survival, feed conversion and shrimp production. A systematic review was carried out using specific keywords in relevant scientific databases, which made it possible to collect updated and relevant information on the topic. The discussion focuses on the importance of phytoplankton as a primary producer, its influence on water quality and its role in the diet of shrimp. Recommendations for maintaining a beneficial balance of phytoplankton communities in cropping systems are detailed. Furthermore, the role of zooplankton as a crucial link in the food chain is analyzed, providing recommendations on the desirable amount of zooplankton in semi-intensive farming. Strategies to address challenges related to primary productivity and food chains in culture ponds are also discussed. In conclusion, this study highlights the importance of the ecosystem approach in shrimp farming, underlining the need to understand and manage planktonic communities to achieve successful and sustainable aquaculture.